Development of an algorithm for gamma dose mapping in irradiated product using TOPSIS and its validation. (December 2020) - Singh, Meghraj; Datta, D.
Abstract: Achieving technological perseverance and retention of quality of the products are being carried out through gamma irradiation. The conventional methodology for dose mapping in products is a complex and time-consuming process. In general, the operator spends lots of time to gain experience and fix the optimal irradiation parameters. Considering the complex geometrical configuration of product box and source, an efficient and simple methodology is needed for estimating dose profile. The estimation of various process parameters for product irradiation such as dose uniformity ratio, minimum and maximum dose is pre-requisite for routine operation. The irradiation process starts with the transport of identical product boxes to the irradiation cell through a guided path. The carriers are irradiated at known positions in the cell for the ideal process conditions defined by various parameters such as the bulk density of product, distance from the source, conveyer speed, duration of irradiation, irradiation temperature, etc. This research proposes a multi-criteria decision-making methodology to select the best strategy for dose mapping. Analytical Hierarchy Process (AHP) and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) have been used to optimize the process variables. To validate the robustness of the proposed methodology, the experimental data set has been generated during the commissioning of the desired configuration of source and product using a leave-one-out strategy. The proposed methodology has been applied for dosimetry of homogeneous product containing sawdust and rice husk. The dose uniformity ratio using the proposed methodology is found to be better than the conventional commissioning dosimeter. The statistical parameters can be evaluated with the Y-set in contrary to that of obtained from the Z set of conventional methods. The methodology is generic and can help the operator with/without experience, while mapping dose in products. Highlights: An algorithm based on AHP & TOPSIS is used for the map of gamma dose in gamma irradiator. The algorithm is validated during commissioning dosimetry of gamma irradiator. The proposed algorithm is faster than convention dosimetry procedure. Z-set of dose mapping may be avoided using the proposed algorithm. Operating parameters and throughput of gamma irradiator can better optimize.